2009 Florida Land Value Survey: Farm Land Prices Remain Down - Rodney L. Clouser; Ronald P. Muraro; Laila Racevskis; Charles Moss; Robert A. Morris (EDIS, 2010)
FE833, a 7-page report by Rodney L. Clouser, Ronald Muraro, Laila Racevskis, Charles Moss, and Robert A. Morris, presents the results of the 2009 land value survey to estimate the value of different types of agricultural land for geographic regions of the state. Includes references. Published by the UF Department of Food and Resource Economics, March 2010.